2017
DOI: 10.5812/ijcm.10235
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gender-Specific Lung Cancer Deaths due to Exposure to PM2.5 in 10 Cities of Iran During 2013 - 2016: A Modeling Approach

Abstract: Background: Various epidemiological studies have related fine particles (PM2.5) to incidence of lung cancer. In addition, particulate air pollution has been classified as Group 1 carcinogen by international agency for research on cancer (IARC) in 2013. Objectives: The aim of this study was to quantify the number of gender-specific lung cancer deaths due to exposure to PM2.5 among individuals aged over 30 years using WHO AirQ+ model in 10 cities of Iran during March 2013-March 2016. Methods: Hourly concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Studies about the use of AirQ+ are very rare (Hadei et al, 2017a(Hadei et al, , 2017c; however, many studies can be found about the quantification of health effects attributable to air pollution using the AirQ 2.2.3 model. Hadei et al (2013) estimated short-term mortality attributable to various air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about the use of AirQ+ are very rare (Hadei et al, 2017a(Hadei et al, , 2017c; however, many studies can be found about the quantification of health effects attributable to air pollution using the AirQ 2.2.3 model. Hadei et al (2013) estimated short-term mortality attributable to various air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study in Tehran, air pollution, dust and the presence of pollutants in the environment are associated with an increased risk of LC mortality ( 57 ) and suspended particles below 2.5 micron has been identified as a risk factor for LC with a coefficient of 0.43 ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…The optional input data included latitude, longitude, and location identification. We assessed different health-related results using this software tool, including the attributable proportion of cases, the number of attributable cases, the number of attributable cases per 100,000 population at risk, the proportion of cases in the pollutant concentration range, and the cumulative distribution by air pollutant concentration [16,31,32]. We also used Origin (version 2020) to plot bar charts for the attributable cases of mortality and hospital admissions.…”
Section: Data Sampling and Analysismentioning
confidence: 99%